Flame-retardant and anti-shrinkage coating self-crosslinking lithium battery separator and its molding process
By preparing a modified silica-coated alumina containing long-chain fatty acids and a polyurethane emulsion coating modified with terminal aminotriethoxysilane on the lithium battery separator, the problem of flammability and shrinkage of the lithium battery separator is solved, and the safety and service life of the battery are improved.
Patent Information
- Application Number
- CN202510685661.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-27
- Publication Date
- 2025-09-16
- Estimated Expiration
- 2045-05-27
AI Technical Summary
Existing lithium battery separators are flammable and easy to shrink, affecting battery safety and service life.
A flame-retardant and anti-shrinkage coating self-crosslinked lithium battery separator is used. The coating is composed of modified silica-coated alumina containing long-chain fatty acids, polyurethane emulsion modified with end-amino triethoxysilane, defoaming agent polydimethylsiloxane and thickener sodium carboxymethyl cellulose. It is prepared through a specific process to enhance the insulation and anti-shrinkage properties of the separator.
The flame retardant and shrinkage resistance of lithium batteries are improved, and the service life of the batteries is extended.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of battery materials, in particular to a flame-retardant and anti-shrinkage coating self-crosslinking lithium battery separator and a molding process thereof. Background Art
[0002] With the growing global demand for clean energy, lithium batteries, as efficient and portable energy storage devices, have been widely used in applications such as electric vehicles, consumer electronics, and energy storage systems. In the structure of lithium batteries, the separator is a key internal component, playing an important role in isolating the positive and negative electrodes, preventing short circuits, and providing a migration path for lithium ions during the charge and discharge processes. The performance of the separator directly affects the battery's interface structure, internal resistance, capacity, cycling performance, and safety, and is crucial for improving its overall performance. Currently, the most widely used lithium battery separators in the market are mainly polyolefin-based separators, such as polyethylene (PE) and polypropylene (PP). These separators offer considerable mechanical strength and chemical stability at relatively low cost. However, they have numerous drawbacks in practical applications, including flammability and shrinkage, which can affect battery life. Therefore, developing a lithium battery separator with excellent flame retardancy, good shrinkage resistance, and self-crosslinking properties to improve the safety, stability, and service life of lithium batteries and meet growing market demands has become a key challenge in the lithium battery industry. Summary of the Invention
[0003] In view of the deficiencies of the prior art, the present invention provides a flame-retardant and anti-shrinkage coating self-crosslinking lithium battery separator and a molding process thereof.
[0004] To achieve the above object, the present invention provides the following technical solution: a flame retardant and anti-shrinkage coating self-crosslinking lithium battery separator, wherein the lithium battery separator is composed of a battery base film and a coating applied on both sides of the base film;
[0005] The battery base membrane is composed of the following raw materials by weight: 80-120 parts of polypropylene fiber, 5-10 parts of sodium dodecylbenzene sulfonate and 1-3 parts of polydimethylsiloxane;
[0006] The coating is composed of the following raw materials by weight: 10-20 parts of modified silica-coated alumina containing long-chain fatty acids, 80-150 parts of polyurethane emulsion modified with aminotriethoxysilane, 3-5 parts of defoaming agent polydimethylsiloxane, and 2-4 parts of thickener sodium carboxymethyl cellulose.
[0007] Preferably, the coating is prepared by the following steps:
[0008] S1. Ultrasonic cleaning of aluminum oxide in an ethanol solution for 3-5 minutes, vacuum drying to constant weight, and placing in the ALD equipment reaction chamber. The chamber is heated to 100-200°C, nitrogen is passed through, and cyclic deposition is performed. Silicon tetrachloride is passed through in pulse one and oxygen is passed through in pulse two. After repeating the pulse operation 50-100 times, annealing is performed in air at 300-500°C for 1-3 hours to obtain silicon dioxide-coated aluminum oxide.
[0009] S2, dissolving aminosilane in a water-ethanol mixture with a volume ratio of 1:9, adjusting the pH to 3-5 with acetic acid, adding silica-coated alumina, stirring and refluxing at 50-80°C for 3-8 hours, washing with ethanol 3-5 times, and vacuum drying at 60-80°C overnight to obtain amino-modified silica-coated alumina;
[0010] S3, mixing amino-modified silica-coated alumina, acrylate, and p-toluenesulfonic acid, passing nitrogen, vigorously stirring at 100-120°C for 10-16 hours, then evacuating the mixture for 30-60 minutes, washing with methanol, centrifuging the precipitate, and vacuum drying to obtain acrylate-grafted amino-modified silica-coated alumina;
[0011] S4, mixing hydroxypalmitic acid and acrylate grafted amino-modified silica-coated alumina, passing argon, slowly adding a phosphazene base catalyst, reacting at 20-30°C for 1-3 hours, and adding acetic acid to terminate the reaction to obtain modified silica-coated alumina containing long-chain fatty acids;
[0012] S5. Place diethylenetriamine in an ice-water bath, purge with nitrogen, slowly add vinyltriethoxysilane, react at 20-30°C for 1-4 h, raise the temperature to 120-160°C and react under reduced pressure for 2-5 h to obtain amino-terminated triethoxysilane;
[0013] S6. Place the polyether polyol in an environment of 100-110°C for vacuum dehydration, cool to 40-50°C, add isophorone diisocyanate, aminotriethoxysilane and catalyst dibutyltin dilaurate, pass nitrogen, heat to 70-80°C, react for 1-3 hours, cool to 50-60°C, add trimethylolpropane and continue to react for 30-60 minutes, cool to 30-35°C, add triethylamine for neutralization, and add deionized water for emulsification to obtain a polyurethane emulsion modified with aminotriethoxysilane;
[0014] S7. Add modified silica-coated alumina containing long-chain fatty acids to a polyurethane emulsion modified with terminal aminotriethoxysilane, add a defoamer and a thickener, and stir at 20-30° C. for 10-30 min to obtain a coating having a thickness of 3-8 μm.
[0015] Preferably, in step S2, the mass ratio of aminosilane to silica-coated alumina is 0.5-5:100.
[0016] Preferably, in step S3, the mass ratio of amino-modified silica-coated alumina, acrylate, and p-toluenesulfonic acid is 1:0.2-0.4:0.05-0.1.
[0017] Preferably, in step S4, the mass ratio of hydroxypalmitic acid, acrylate grafted amino-modified silica-coated alumina mixture, catalyst phosphazene base, and acetic acid is 1:2-4:0.2-0.5:5-10.
[0018] Preferably, in step S5, the mass ratio of diethylenetriamine to vinyltriethoxysilane is 1:0.8-1.
[0019] Preferably, in step S6, the mass ratio of polyether polyol, isophorone diisocyanate, amino-terminated triethoxysilane, catalyst dibutyltin dilaurate, trimethylolpropane, triethylamine, and deionized water is 1:0.5~0.8:0.1~0.3:0.03~0.05:0.05~0.08:0.07~0.1:5~8.
[0020] Preferably, the polyether polyol in step S6 is one of polyoxypropylene glycol, polyoxypropylene triol or polytetramethylene glycol.
[0021] Preferably, the battery base membrane preparation steps are as follows: adding polypropylene fiber to the drum of a fiber deflaking machine, adding sodium dodecylbenzene sulfonate and polydimethylsiloxane, adding water, deflaking at 18000~26000 rpm for 10~20 min, forming the sheet in a standard paper sheet former, drying the paper sheet, and hot pressing to obtain a battery base membrane, wherein the battery base membrane has a thickness of 10~30 μm.
[0022] Preferably, the method comprises the following steps: applying the coating on both sides of the battery base film, curing at 100-200° C. for 1-3 hours, and cooling by a cooling roller to obtain a flame-retardant and shrinkage-resistant coating self-crosslinking lithium battery separator.
[0023] Alumina is subjected to cyclic deposition to obtain silica-coated alumina. The surface is modified with aminosilane to obtain amino-modified silica-coated alumina. The amino groups are then reacted with ester groups of acrylates for grafting to obtain acrylate-grafted amino-modified silica-coated alumina. The hydroxyl groups of hydroxypalmitic acid and carbon-carbon double bonds undergo Michael addition polymerization using a phosphazene base catalyst to obtain a modified silica-coated alumina containing long-chain fatty acids. Vinyltriethoxysilane is modified with amino groups, and the modified aminotriethoxysilane is then used to modify polyurethane to obtain an aminotriethoxysilane-modified polyurethane emulsion. The modified silica-coated alumina containing long-chain fatty acids, the aminotriethoxysilane-modified polyurethane emulsion, the defoaming agent polydimethylsiloxane, and the thickener sodium carboxymethylcellulose are mixed to obtain a coating.
[0024] The carboxyl and amino groups of the modified silica-coated alumina containing long-chain fatty acids and the amino-terminated triethoxysilane-modified polyurethane emulsion react, increasing their compatibility. The silica-coated alumina enhances the insulation properties of the separator, effectively extending battery life. The long-chain fatty acids and siloxane improve the separator's shrinkage resistance. Furthermore, the long-chain fatty acids and modified siloxanes increase compatibility, improve bonding, and stabilize the coating.
[0025] The lithium battery separator of the present invention has good flame retardancy and shrinkage resistance, and can effectively improve the service life of the battery. DETAILED DESCRIPTION
[0026] Example 1: This example provides a flame-retardant, anti-shrinkage coating self-crosslinking lithium battery separator, which consists of a battery base film and a coating applied on both sides of the base film;
[0027] The battery base film is composed of the following raw materials by weight: 80 parts of polypropylene fiber, 5 parts of sodium dodecylbenzene sulfonate and 1 part of polydimethylsiloxane;
[0028] The coating consists of the following raw materials by weight: 10 parts of modified silica-coated alumina containing long-chain fatty acids, 80 parts of polyurethane emulsion modified with terminal aminotriethoxysilane, 3 parts of defoaming agent polydimethylsiloxane, and 2 parts of thickener sodium carboxymethyl cellulose.
[0029] In this embodiment, it should be noted that the components of the lithium battery separator formula of the present invention are all commercially available unless otherwise specified.
[0030] The steps for preparing the coating are as follows:
[0031] S1. Ultrasonic cleaning of alumina was performed in an ethanol solution for 3 minutes, followed by vacuum drying to constant weight. The alumina was placed in the reaction chamber of the ALD equipment. The chamber was heated to 100°C and nitrogen was introduced for cyclic deposition. Silicon tetrachloride was introduced in pulse one and oxygen was introduced in pulse two. The pulse operation was repeated 50 times, and the alumina was annealed in air at 300°C for 1 hour to obtain silica-coated alumina.
[0032] S2. Dissolve aminosilane in 400 mL of a water-ethanol mixture with a volume ratio of 1:9, adjust the pH to 3 with acetic acid, add silica-coated alumina, stir and reflux at 50°C for 3 h, wash with ethanol three times, and vacuum dry at 60°C overnight to obtain amino-modified silica-coated alumina.
[0033] S3. Mix amino-modified silica-coated alumina, acrylate, and p-toluenesulfonic acid, pass nitrogen, vigorously stir at 100°C for 10 h, then evacuate for 30 min, wash with methanol, centrifuge and precipitate, and vacuum dry to obtain acrylate-grafted amino-modified silica-coated alumina.
[0034] S4. Mix hydroxypalmitic acid and acrylate-grafted amino-modified silica-coated alumina, pass argon, slowly add catalyst phosphazene base, react at 20°C for 1 hour, and add 100 g of acetic acid to terminate the reaction to obtain modified silica-coated alumina containing long-chain fatty acids.
[0035] S5. Place diethylenetriamine in an ice-water bath, pass nitrogen, slowly add vinyltriethoxysilane, react at 20°C for 1 h, heat to 120°C and react under reduced pressure for 2 h to obtain amino-terminated triethoxysilane.
[0036] S6. Place polyoxypropylene glycol in a 100°C environment for vacuum dehydration, cool to 40°C, add isophorone diisocyanate, terminal aminotriethoxysilane and catalyst dibutyltin dilaurate, pass nitrogen, raise the temperature to 70°C, react for 1 hour, cool to 50°C, add 10 g of trimethylolpropane and continue to react for 30 minutes, cool to 30°C, add triethylamine for neutralization, add 1000 mL of deionized water for emulsification, and obtain a terminal aminotriethoxysilane-modified polyurethane emulsion.
[0037] S7. Add modified silica-coated alumina containing long-chain fatty acids to a polyurethane emulsion modified with terminal aminotriethoxysilane, add a defoaming agent polydimethylsiloxane and a thickener sodium carboxymethyl cellulose, and stir at 20°C for 10 minutes to obtain a coating with a coating thickness of 3 μm.
[0038] The steps for preparing the battery base membrane are as follows: add polypropylene fiber to the drum of a fiber defiberizer, add sodium dodecylbenzene sulfonate and polydimethylsiloxane, add water, defiberize at 18,000 rpm for 10 minutes, form the paper sheets in a standard paper former, dry the paper sheets, and hot press to obtain a battery base membrane with a thickness of 10 μm.
[0039] The molding process of the flame-retardant and anti-shrinkage coating self-crosslinking lithium battery separator comprises the following steps: applying the coating on both sides of the battery base film, curing at 100° C. for 1 hour, and cooling by a cooling roller to obtain the flame-retardant and anti-shrinkage coating self-crosslinking lithium battery separator.
[0040] Example 2: This example provides a flame-retardant, anti-shrinkage coating self-crosslinking lithium battery separator, which consists of a battery base film and a coating applied on both sides of the base film;
[0041] The battery base film is composed of the following raw materials by weight: 100 parts of polypropylene fiber, 80 parts of sodium dodecylbenzene sulfonate and 2 parts of polydimethylsiloxane;
[0042] The coating consists of the following raw materials by weight: 15 parts of modified silica-coated alumina containing long-chain fatty acids, 120 parts of polyurethane emulsion modified with terminal aminotriethoxysilane, 4 parts of defoaming agent polydimethylsiloxane, and 3 parts of thickener sodium carboxymethyl cellulose.
[0043] In this embodiment, it should be noted that the components of the lithium battery separator formula of the present invention are all commercially available unless otherwise specified.
[0044] The steps for preparing the coating are as follows:
[0045] S1. Ultrasonic cleaning of aluminum oxide was performed in an ethanol solution for 5 minutes, followed by vacuum drying to constant weight. The aluminum oxide was placed in the reaction chamber of the ALD equipment. The chamber was heated to 180°C and nitrogen was introduced for cyclic deposition. Silicon tetrachloride was introduced in pulse one and oxygen was introduced in pulse two. The pulse operation was repeated 100 times, and the aluminum oxide was annealed in air at 300°C for 1 hour to obtain silicon dioxide-coated aluminum oxide.
[0046] S2. Dissolve aminosilane in 600 mL of a water-ethanol mixture with a volume ratio of 1:9, adjust the pH to 3 with acetic acid, add silica-coated alumina, stir and reflux at 70°C for 6 h, wash with ethanol three times, and vacuum dry at 80°C overnight to obtain amino-modified silica-coated alumina.
[0047] S3. Mix amino-modified silica-coated alumina, acrylate, and p-toluenesulfonic acid, pass nitrogen, vigorously stir at 100°C for 15 hours, then evacuate for 50 minutes, wash with methanol, centrifuge and precipitate, and vacuum dry to obtain acrylate-grafted amino-modified silica-coated alumina.
[0048] S4. Mix hydroxypalmitic acid and acrylate grafted amino-modified silica-coated alumina, pass argon, slowly add catalyst phosphazene base, react at 30°C for 3 h, add acetic acid to terminate the reaction, and obtain modified silica-coated alumina containing long-chain fatty acids.
[0049] S5. Place diethylenetriamine in an ice-water bath, pass nitrogen, slowly add 1g vinyltriethoxysilane, react at 20°C for 2 h, heat to 140°C and react under reduced pressure for 4 h to obtain amino-terminated triethoxysilane.
[0050] S6. Place polyoxypropylene glycol in a 110°C environment for vacuum dehydration, cool to 40°C, add isophorone diisocyanate, terminal aminotriethoxysilane and catalyst dibutyltin dilaurate, pass nitrogen, raise the temperature to 80°C, react for 2 hours, cool to 60°C, add trimethylolpropane and continue to react for 60 minutes, cool to 35°C, add triethylamine for neutralization, add 1500 mL of deionized water for emulsification, and obtain a terminal aminotriethoxysilane-modified polyurethane emulsion.
[0051] S7. Add modified silica-coated alumina containing long-chain fatty acids to a polyurethane emulsion modified with terminal aminotriethoxysilane, add a defoaming agent polydimethylsiloxane and a thickener sodium carboxymethyl cellulose, and stir at 30°C for 10 minutes to obtain a coating with a coating thickness of 3 μm.
[0052] The steps for preparing the battery base membrane are as follows: add polypropylene fiber to the drum of a fiber defiberizer, add sodium dodecylbenzene sulfonate and polydimethylsiloxane, add 2 L of water, defiberize at 20,000 rpm for 15 minutes, form the sheet in a standard paper former, dry the paper sheet, and hot press to obtain a battery base membrane with a thickness of 15 μm.
[0053] The molding process of the flame-retardant and anti-shrinkage coating self-crosslinking lithium battery separator includes the following steps: applying the coating on both sides of the base film, curing at 120° C. for 1 hour, and cooling by a cooling roller to obtain the flame-retardant and anti-shrinkage coating self-crosslinking lithium battery separator.
[0054] Example 3: This example provides a flame-retardant, anti-shrinkage coating self-crosslinking lithium battery separator, which consists of a battery base film and a coating applied on both sides of the base film;
[0055] The battery base film is composed of the following raw materials by weight: 120 parts of polypropylene fiber, 10 parts of sodium dodecylbenzene sulfonate and 3 parts of polydimethylsiloxane;
[0056] The coating consists of the following raw materials by weight: 10 parts of modified silica-coated alumina containing long-chain fatty acids, 150 parts of polyurethane emulsion modified with terminal aminotriethoxysilane, 5 parts of defoaming agent polydimethylsiloxane, and 4 parts of thickener sodium carboxymethyl cellulose.
[0057] In this embodiment, it should be noted that the components of the lithium battery separator formula of the present invention are all commercially available unless otherwise specified.
[0058] The steps for preparing the coating are as follows:
[0059] S1. Ultrasonic cleaning of aluminum oxide was performed in an ethanol solution for 5 minutes, followed by vacuum drying to constant weight. The aluminum oxide was placed in the reaction chamber of the ALD equipment. The chamber was heated to 200°C and nitrogen was introduced for cyclic deposition. Silicon tetrachloride was introduced in pulse one and oxygen was introduced in pulse two. The pulse operation was repeated 100 times, and the aluminum oxide was annealed in air at 500°C for 3 hours to obtain silicon dioxide-coated aluminum oxide.
[0060] S2. Dissolve aminosilane in 800 mL of a water-ethanol mixture with a volume ratio of 1:9, adjust the pH to 5 with acetic acid, add silica-coated alumina, stir and reflux at 80°C for 8 h, wash with ethanol 5 times, and vacuum dry at 80°C overnight to obtain amino-modified silica-coated alumina.
[0061] S3. Mix amino-modified silica-coated alumina, acrylate, and p-toluenesulfonic acid, pass nitrogen, vigorously stir at 120°C for 16 hours, then evacuate for 60 minutes, wash with methanol, centrifuge and precipitate, and vacuum dry to obtain acrylate-grafted amino-modified silica-coated alumina.
[0062] S4. Mix hydroxypalmitic acid and acrylate grafted amino-modified silica-coated alumina, pass argon, slowly add catalyst phosphazene base, react at 30°C for 3 h, add acetic acid to terminate the reaction, and obtain modified silica-coated alumina containing long-chain fatty acids.
[0063] S5. Place diethylenetriamine in an ice-water bath, pass nitrogen, slowly add vinyltriethoxysilane, react at 30°C for 4 h, heat to 160°C and react under reduced pressure for 5 h to obtain amino-terminated triethoxysilane.
[0064] S6. Place polyoxypropylene triol in a 110°C environment for vacuum dehydration, cool to 50°C, add isophorone diisocyanate, terminal aminotriethoxysilane and catalyst dibutyltin dilaurate, pass nitrogen, raise the temperature to 80°C, react for 3 hours, cool to 60°C, add trimethylolpropane and continue to react for 60 minutes, cool to 35°C, add triethylamine for neutralization, add 1600 mL of deionized water for emulsification, and obtain a terminal aminotriethoxysilane-modified polyurethane emulsion.
[0065] S7. Add modified silica-coated alumina containing long-chain fatty acids to a polyurethane emulsion modified with terminal aminotriethoxysilane, add a defoaming agent polydimethylsiloxane and a thickener sodium carboxymethyl cellulose, and stir at 30°C for 30 minutes to obtain a coating with a coating thickness of 8 μm.
[0066] The steps for preparing the battery base membrane are as follows: add polypropylene fiber to the drum of a fiber defiber machine, add sodium dodecylbenzene sulfonate and polydimethylsiloxane, add 2 L of water, defiberize at 26,000 rpm for 20 minutes, form the paper sheets in a standard paper former, dry the paper sheets, and hot press to obtain a battery base membrane with a thickness of 30 μm.
[0067] The molding process of the flame-retardant and anti-shrinkage coating self-crosslinking lithium battery separator comprises the following steps: applying the coating on both sides of the battery base film, curing at 200° C. for 3 hours, and cooling by a cooling roller to obtain the flame-retardant and anti-shrinkage coating self-crosslinking lithium battery separator.
[0068] Comparative Example 1: The modified silica-coated alumina containing long-chain fatty acids prepared in steps S1-S4 was omitted, hydroxypalmitic acid was added alone, and the rest of the process was the same as in Example 1.
[0069] Comparative Example 2: The polyurethane was not modified, and the remaining processes were the same as in Example 1.
[0070] Comparative Example 3: No hydroxypalmitic acid was added, and the rest of the process was the same as in Example 1.
[0071] Comparative Example 4: Silicon dioxide and aluminum oxide were blended, and the rest of the process was the same as in Example 1.
[0072] Performance testing:
[0073] 1. Flame retardancy and shrinkage resistance test: Examples 1 to 3 and Comparative Examples 1 to 3 were subjected to longitudinal and transverse shrinkage rate tests. The samples were heated at 280°C for 12 hours to measure the changes in longitudinal and transverse dimensions before and after heating. The limiting oxygen index test was conducted in accordance with JIS-K7201-3-2008.
[0074] 2. Storage performance test: A high temperature (45°C) cyclic charge and discharge experiment was conducted on a lithium iron phosphate battery prepared using the lithium battery separators prepared in Examples 1 to 5 and Comparative Example 3.
[0075] The test results are recorded in Table 1.
[0076]
[0077] As can be seen from Table 1, compared with the examples, Comparative Example 1 does not add nano-ceramic materials silica and alumina, and the transverse and longitudinal shrinkage rates are higher than those of the examples, and the limiting oxygen index is lower than that of the examples, indicating that the addition of silica and alumina can effectively improve the flame retardant and shrinkage resistance of the lithium battery separator. Compared with the examples, Comparative Example 2 does not modify the polyurethane, and the transverse and longitudinal shrinkage rates are higher than those of the examples, and the limiting oxygen index is lower than that of the examples, indicating that the modified polyurethane can effectively improve the flame retardant and shrinkage resistance of the lithium battery separator. Compared with the examples, Comparative Example 3 has basically the same shrinkage rate and a lower limiting oxygen index, indicating that the addition of hydroxypalmitic acid can improve the shrinkage resistance of the separator. Compared with the examples, Comparative Example 4 has a different combination of silica and alumina. The charge retention rate of Comparative Example 3 is lower than that of the examples, indicating that silica-coated alumina can effectively improve battery storage performance and service life.
[0078] While embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions, and variations may be made to these embodiments without departing from the principles and spirit of the invention, and that the scope of the invention is defined by the appended claims and their equivalents.
Claims
1. Flame retardant and anti-shrinkage coating self-crosslinking lithium battery separator, characterized in that: The lithium battery separator is composed of a battery base film and a coating layer coated on both sides of the base film; The battery base membrane is composed of the following raw materials by weight: 80-120 parts of polypropylene fiber, 5-10 parts of sodium dodecylbenzene sulfonate and 1-3 parts of polydimethylsiloxane; The coating is composed of the following raw materials by weight: 10-20 parts of modified silica-coated alumina containing long-chain fatty acids, 80-150 parts of a polyurethane emulsion modified with aminotriethoxysilane, 3-5 parts of a defoaming agent, polydimethylsiloxane, and 2-4 parts of a thickener, sodium carboxymethyl cellulose. The steps for preparing the coating are as follows: S1. Ultrasonic cleaning of aluminum oxide in an ethanol solution for 3-5 minutes, vacuum drying to constant weight, and placing in the ALD equipment reaction chamber. The chamber is heated to 100-200°C, nitrogen is passed through, and cyclic deposition is performed. Silicon tetrachloride is passed through in pulse one and oxygen is passed through in pulse two. After repeating the pulse operation 50-100 times, annealing is performed in air at 300-500°C for 1-3 hours to obtain silicon dioxide-coated aluminum oxide. S2, dissolving aminosilane in a water-ethanol mixture with a volume ratio of 1:9, adjusting the pH to 3-5 with acetic acid, adding silica-coated alumina, stirring and refluxing at 50-80°C for 3-8 hours, washing with ethanol 3-5 times, and vacuum drying at 60-80°C overnight to obtain amino-modified silica-coated alumina; S3, mixing amino-modified silica-coated alumina, acrylate, and p-toluenesulfonic acid, passing nitrogen, vigorously stirring at 100-120°C for 10-16 hours, then evacuating the mixture for 30-60 minutes, washing with methanol, centrifuging the precipitate, and vacuum drying to obtain acrylate-grafted amino-modified silica-coated alumina; S4, mixing hydroxypalmitic acid and acrylate grafted amino-modified silica-coated alumina, passing argon, slowly adding a phosphazene base catalyst, reacting at 20-30°C for 1-3 hours, and adding acetic acid to terminate the reaction to obtain modified silica-coated alumina containing long-chain fatty acids; S5. Place diethylenetriamine in an ice-water bath, purge with nitrogen, slowly add vinyltriethoxysilane, react at 20-30°C for 1-4 h, raise the temperature to 120-160°C and react under reduced pressure for 2-5 h to obtain amino-terminated triethoxysilane; S6. Place the polyether polyol in an environment of 100-110°C for vacuum dehydration, cool to 40-50°C, add isophorone diisocyanate, aminotriethoxysilane and catalyst dibutyltin dilaurate, pass nitrogen, heat to 70-80°C, react for 1-3 hours, cool to 50-60°C, add trimethylolpropane and continue to react for 30-60 minutes, cool to 30-35°C, add triethylamine for neutralization, and add deionized water for emulsification to obtain a polyurethane emulsion modified with aminotriethoxysilane; S7. Add modified silica-coated alumina containing long-chain fatty acids to a polyurethane emulsion modified with terminal aminotriethoxysilane, add a defoamer and a thickener, and stir at 20-30° C. for 10-30 min to obtain a coating having a thickness of 3-8 μm.
2. The flame-retardant, anti-shrinkage coating self-crosslinking lithium battery separator according to claim 1, characterized in that: In step S2, the mass ratio of aminosilane to silica-coated alumina is 0.5-5:
100.
3. The flame-retardant, anti-shrinkage coating self-crosslinking lithium battery separator according to claim 1, characterized in that: In step S3, the mass ratio of amino-modified silica-coated alumina, acrylate, and p-toluenesulfonic acid is 1:0.2-0.4:0.05-0.
1.
4. The flame-retardant, anti-shrinkage coating self-crosslinking lithium battery separator according to claim 1, characterized in that: In step S4, the mass ratio of hydroxypalmitic acid, acrylate grafted amino-modified silica-coated alumina, catalyst phosphazene base, and acetic acid is 1:2-4:0.2-0.5:5-10.
5. The flame-retardant, anti-shrinkage coating self-crosslinking lithium battery separator according to claim 1, characterized in that: In step S5, the mass ratio of diethylenetriamine to vinyltriethoxysilane is 1:0.8-1.
6. The flame-retardant, anti-shrinkage coating self-crosslinking lithium battery separator according to claim 1, characterized in that: In step S6, the mass ratio of polyether polyol, isophorone diisocyanate, amino-terminated triethoxysilane, catalyst dibutyltin dilaurate, trimethylolpropane, triethylamine, and deionized water is 1:0.5-0.8:0.1-0.3:0.03-0.05:0.05-0.08:0.07-0.1:5-8.
7. The flame-retardant, anti-shrinkage coating self-crosslinking lithium battery separator according to claim 1, characterized in that: In the step S6, the polyether polyol is one of polyoxypropylene glycol, polyoxypropylene triol or polytetrahydrofuran diol.
8. The flame retardant and shrinkage-resistant self-crosslinking lithium battery separator according to claim 1, characterized in that: The battery base membrane preparation steps are as follows: adding polypropylene fiber to the drum of a fiber deflaking machine, adding sodium dodecylbenzene sulfonate and polydimethylsiloxane, adding water, deflaking at 18000-26000 rpm for 10-20 minutes, forming the sheet in a standard paper sheet former, drying the paper sheet, and hot pressing to obtain the battery base membrane, wherein the battery base membrane has a thickness of 10-30 μm.
9. The molding process of the flame retardant and shrinkage-resistant self-crosslinking lithium battery separator according to any one of claims 1 to 8, characterized in that: The method comprises the following steps: applying the coating on both sides of the battery base film, curing the coating at 100-200°C for 1-3 hours, and cooling the coating by a cooling roller to obtain a flame-retardant and anti-shrinkage coating self-crosslinking lithium battery separator.
Citation Information
Patent Citations
Preparation method of surface-modified aluminum oxide ceramic coating diaphragm
CN110600660A
Flame-retardant lithium battery diaphragm and preparation method thereof
CN118367302A